2011
DOI: 10.1371/journal.pone.0024663
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PI3K Prevents the Proliferation and Differentiation of Human Lung Fibroblasts into Myofibroblasts: The Role of Class I P110 Isoforms

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive fibroproliferative disease characterized by an accumulation of fibroblasts and myofibroblasts in the alveolar wall. Even though the pathogenesis of this fatal disorder remains unclear, transforming growth factor-β (TGF-β)-induced differentiation and proliferation of myofibroblasts is recognized as a primary event. The molecular pathways involved in TGF-β signalling are generally Smad-dependent yet Smad-independent pathways, including phosphatidylinositol-3-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(106 citation statements)
references
References 24 publications
3
94
0
Order By: Relevance
“…S4 and S5). Consistently, Conte et al have shown that LY294002 can also inhibit myofibroblast differentiation of human lung fibroblasts on TCPS (24). The PI3K/AKT pathway is not only necessary for myofibroblast activation on stiff substrates; endogenous AKT activation .…”
Section: Discussionmentioning
confidence: 68%
“…S4 and S5). Consistently, Conte et al have shown that LY294002 can also inhibit myofibroblast differentiation of human lung fibroblasts on TCPS (24). The PI3K/AKT pathway is not only necessary for myofibroblast activation on stiff substrates; endogenous AKT activation .…”
Section: Discussionmentioning
confidence: 68%
“…ROS can act as both an upstream and downstream mediator of PDGFR phosphorylation, and the involvement of mitochondrial ROS in PDGFR activation has been reported in cases of autophagy inhibition (22). Furthermore, PI3K/AKT activation (which is downstream of the PDGFR signaling pathway) participates in the regulation of myofibroblast differentiation (23,24). ATG5 knockdown-mediated activation of the PDGFRs/PI3K/AKT signaling pathway was elucidated by the detection of phosphorylated forms of PDGFRs, PI3K, and AKT by Western blotting (Fig.…”
Section: Atg5 Knockdown Induces Mitochondrial Ros Production Activatmentioning
confidence: 99%
“…The small interfering RNA (siRNA)-mediated specific knockdown of PI3K (class I) was applied to inhibit the activation of downstream Akt. Scramble siRNA, a non-functional and non-targeting siRNA, was used as the control group [35]. The results showed that TMP significantly suppressed PI3K (class I) and blocked downstream Akt activation.…”
Section: Tmp Completely Reversed the Apoptotic Detrimental Effects Inmentioning
confidence: 99%